Electronic Criminal Case Trial from the Perspective of Justice and Legal Certainty - Kiki Indrawan; Suryansyah Marhaini; Mutia Evi Kristhy; Kiki Kristanto (Budapest International Research and Critics University, 2021)
The Covid-19 pandemic that hit Indonesia has caused major changes in the legal world. The enactment of social distancing/physical distancing rules and Large-Scale Social Restrictions (PSBB) ultimately forced the Supreme Court to make a legal breakthrough by issuing PERMA No. 4 of 2020 concerning the Administration and Trial of Criminal Cases in Courts Electronically, the purpose of which is to fill the legal vacuum in the Criminal Procedure Code and guarantee the right of the accused to immediately obtain legal certainty for the crime he is accused of through trial without undue delay, with fair treatment. and impartiality (fair trial) , which is a guarantee for the protection of the rights of everyone in the judicial process. PERMA No. 4 of 2020 concerning the Administration and Trial of Criminal Cases in Courts Electronically guarantees a fair and impartial electronic trial that meets the principles of justice and legal certainty, by clearly stipulating the rights of defendants in electronic criminal case trials, namely the right to obtain legal assistance, the right to defend, the right to be tried in a court session which is open to the public, and the right to immediately receive an examination in court for legal certainty. Then to fill the legal vacuum in the Criminal Procedure Code, and in the future, electronic criminal case trials must be strictly regulated to become the new norm in the revision of the Criminal Procedure Code.